2022
DOI: 10.1186/s12872-022-03016-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of LDL to HDL ratio with new-onset atrial fibrillation after on-pump coronary artery bypass graft surgery

Abstract: Objective This study aims to analyze the association between preoperative LDL/HDL ratio and new-onset atrial fibrillation (AF) after on-pump coronary artery bypass grafting (on-pump CABG), evaluate the clinic value of preoperative LDL/HDL ratio to identify postoperative rhythm. Methods A retrospective study of consecutive patients (n = 2052) who underwent on-pump CABG at TEDA International Cardiovascular Hospital (Tianjin, China), from June 1, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies have shown an inverse relationship between the LDL-C/HDL-C ratio and the development of AF, particularly in individuals aged 75 and older 25,32 . Moreover, research involving coronary artery bypass graft patients revealed a higher incidence of postoperative AF with elevated LDL-C/HDL-C ratios, notably in women 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an inverse relationship between the LDL-C/HDL-C ratio and the development of AF, particularly in individuals aged 75 and older 25,32 . Moreover, research involving coronary artery bypass graft patients revealed a higher incidence of postoperative AF with elevated LDL-C/HDL-C ratios, notably in women 33 .…”
Section: Introductionmentioning
confidence: 99%